Effect of Environmental Performance on Environmental Disclosures of Manufacturing, Mining and Plantation Companies Listed in Indonesia Stock Exchange - Rudi Kurniawan (Arthatama, 2017)
The issuance of Government Regulation No. 47 of 2012 on Social and Environmental Responsibility enables companies to take account of their activities in the social and environmental field and to report in the company's annual report. This study aims to obtain empirical evidence about the effect of environmental performance on environmental disclosure with Government Regulation. 47 of 2012 as a moderating variable. In this study, the variable of environmental performance was measured using Corporate Performance Rating Assessment Program (PROPER) which is one of State Ministry of Environment's efforts to encourage corporate compliance in environmental management through information instruments, and the variable of environmental disclosure was measured by GRI 3.0 (Global Reporting Initiative) score. The variable of Government Regulation No. 47 of 2012 is only used to divide the data group into 2 sub-groups, i.e. groups of data before and after government, regulation was issued. The populations of this research are mining companies, manufactures and plantations listed on the Indonesia Stock Exchange (IDX) and included in PROPER 2010-2013. Technique of collecting data was by using purposive sampling method. The total company in the observation was 92 companies. The hypotheses were tested by using linear regression analysis with moderation variable. The results of this study indicate that environmental performance has a significant positive effect on environmental disclosure, while Government Regulation No. 47 of 2012 has no effect on strengthening the relationship between environmental performance and environmental disclosure.